ACCELERATION OF TEGAL DUCK MOLTING PERIOD AND RE-LAYING USING CATTLE RETICULUM MEAL IN FEED - Rosidi, Rosidi; Yuwanta, T.; Ismaya, Ismaya; Ismoyowati, Ismoyowati (Diponegoro University, 2014)
This research was aimed to evaluate the effect of the level of cattle reticulum meal as cholesterolsource in duck feed to accelerate molting period and post-molting re-laying process of Tegal duck.Experimental method was administered to sixty female Tegal duck aging 68 weeks old. Each treatment,comprised 3 layers with 5 repetitions, were cattle reticulum meal in feed (K), consisting of K0= 0%(control), K1 = 1.43% (equal to 0.37 g cholesterol), K2 = 2.86%, and K3 = 4.29%. The observed variableswere molting period, re-laying period, blood cholesterol level, and progesterone hormone level. Datawere analyzed by analysis of variance based on Completely Randomized Design followed by HonestlySignificant Difference Test. The result demonstrated that level of cattle reticulum meal significantlyaffected (P<0.01) molting period, re-laying period, blood cholesterol and progesterone level. It wasconcluded that 1.43% cattle reticulum meal could accelerate molting period and 2.86% cattle reticulummeal could accelerate re-laying.